IIIT Intellectual Panels at the ISNA 49th Annual Convention - Jay Willoughby (International Institute of Islamic Thought, 2013)
The International Institute of Islamic Thought (IIIT) organized a two-day series of intellectual panels at the Islamic Society of North America’s (ISNA) 49th annual convention, held in Washington, DC over the Labor Day weekend. These events, hosted in the institute’s hospitality suite on the main floor of the Washington Convention Center, took place during 1-2 September 2012. Recently published IIIT books and other selected Arabic and English publications, as well as special collections of the late Ismail Al Faruqi’s works and many of Ali Mazrui’s books, journal articles, and personal items, were also prominently displayed. At the beginning of each session, a documentary on IIIT and its goals was shown ...